A lightweight mutual authentication protocol based on elliptic curve cryptography for IoT devices. (2017) - Tewari, Aakanksha; Gupta, B.B.
The Internet-of-Things (IoT) is an evolving architecture which connects multiple devices to internet for communication or receiving updates from a cloud or a server. In future, the number of these connected devices will increase immensely making them an indistinguishable part of our daily lives. However, these devices in spite of making our lives more comfortable are also making our personal information more at risk. Therefore, security of these devices is also a major concern for us. In this paper, we propose a mutual authentication mechanism between an IoT device and the server based on elliptic curve cryptography (ECC) which gives better solution in terms of communication overhead and attack resistance. Our proposed solution also fulfils the essential requirements of security. The security and performance analysis also verifies the strength of our protocol.